Management of anterior teeth damage caused by complex caries through aesthetic endorestoration - Nanik Zubaidah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Dental caries is a microbiological disease that result in localized dissolution and destruction of the calcified tissue. It is multifactorial, therefore prevention must be based on a multifactorial approach. The damage of anterior teeth due to complex caries, for certain person may interfere their performance and decrease their self confidence aesthetically. Restoration of tooth form and function, especially on anterior teeth is highly valuable. Purpose: To present a case of maxillary anterior teeth with complex caries, through endorestoration treatment for recovering its original function and aesthetic. Case: The 21 years old male patient with complex carries on maxillary anterior teeth number 12, 11, 21, 22 and 23. The patient felt bad about his performance and affect his self confidence. The patient visited the clinic to repair his teeth and to get its form and function aesthetically. Case management: The endorestoration treatment was performed for carious teeth through pulpectomy followed by insertion of post retention and porcelain fused to metal crowns. Conclusion: Anterior teeth with severed complex caries can be managed through endorestoration treatment to recover its performance and function aesthetically.Latar belakang: Dental karies adalah penyakit infeksi yang berakibat kerusakan jaringan kalsifikasi dan bersifat multifactorial. Oleh karena itu pencegahan dilakukan dengan pendekatan multifactorial. Kerusakan gigi anterior karena karies kompleks untuk orang-orang tertentu mungkin berdampak pada penampilan dan penurunan kepercayaan diri karena factor estetik. Perbaikan gigi anterior dari berbagai kerusakan baik dalam hal bentuk maupun fungsinya sangat besar nilainya. Tujuan: Untuk menunjukkan kasus gigi anterior rahang atas karena karies kompleks melalui perawatan endorestorasi untuk mengembalikan fungsi gigi asli dan estetik. Kasus: Laki-laki usia 21 tahun dengan karies kompleks pada gigi anterior rahang atas 12, 11, 21, 22, dan 23. Penderita dating ke klinik untuk perawatan tentang giginya dan mengembalikan bentuk maupun fungsi estetiknya. Tatalaksana kasus: Perawatan endorestorasi dilakukan untuk gigi karies melalui pulpektomi, insersi pasak dan mahkota porselen fuse to metal. Kesimpulan: Gigi dengan karies kompleks yang berat dapat diperbaiki melalui perawatan endorestorasi untuk mengembalikan penampilan dan fungsi estetiknya.